Speckle Interferometric Observations on 2.6 m telescope of BAO - Docobo, J. A.; Gomez, J.; Melikian, N. D.; Paronyan, G.
Speckle observations with a Photon Max EMCCD detector from Princeton Instruments were carried out for the first time in the 2.6 m telescope of BAO. Three observing campaigns were already completed. More than four hundred objects had been observed, relative positions and differential photometry information will be published during next months. Throughout the text we provide general information regarding the campaigns, the camera configuration, the EMCCD technical characteristics, and the reduction procedure. Also a brief discussion on how to determine the angle without the 180º ambiguity is included.
Keywords: Telescope of BAO; Astrometry